Surface eletromiography in the diagnosis of syndromes of the cranio-cervical pain - Fausto Bérzin (Universidade Estadual de Campinas, 2015)
This paper first provides a review of the anatomy and physiology of striated muscles, focusing on the muscle fiber, motor unit and µ neuron. We also commented on the factors that affect the depolarization of this neuron, resulting in its excitation or inhibition, and thereby altering the contractions of the motor unit, which in turn alters the equilibrium of the muscle dynamics. The changes caused by these factors, such as muscular hyperactivity, found mainly in the temporal muscles, with the jaw the resting position and chewing are also discussed. However, muscular hypoactivity is most frequently observed in the masseter muscles. The suprahyoid muscles, responsible for the positioning of the tongue, also show a large number of alterations. We also commented on the changes observed in the contractions of the posterior cranio-cervical musculature, sternocleidomastoid muscles and the upper fibers the trapezius, which are sources of referred pain.